2012
DOI: 10.1521/pedi.2012.26.5.763
|View full text |Cite
|
Sign up to set email alerts
|

Personality Disorder Features Through the Life Course

Abstract: Personality Disorders have proved to be more fluid through the life course than previously thought. However, because analyses have usually been undertaken at the level of diagnostic categories, relevant findings may be obscured. An examination at the criteria level could bypass arbitrary aggregations of heterogeneous traits and thus offer more accurate information. To this end, we administered the Personality Diagnostic Questionnaire-4+ (PDQ-4+) to 1,477 patients aged 15 to 82. Nine of 12 disorders declined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0
9

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 36 publications
2
17
0
9
Order By: Relevance
“…Three studies support the notion that features of personality disorders are susceptible to rank-order and mean-level changes over the course of a person's lifetime (Engels, Duijssens, Harringsma, & van Putten, 2003;Gutiérrez et al, 2012;Ullrich & Coid, 2009). Engels and coworkers (2003) and Ulrich and Coïd (2009) showed an increase of schizoid and obsessive-compulsive traits as a person becomes older.…”
Section: Dsm Personality Disorders: Cross-sectional Resultsmentioning
confidence: 82%
“…Three studies support the notion that features of personality disorders are susceptible to rank-order and mean-level changes over the course of a person's lifetime (Engels, Duijssens, Harringsma, & van Putten, 2003;Gutiérrez et al, 2012;Ullrich & Coid, 2009). Engels and coworkers (2003) and Ulrich and Coïd (2009) showed an increase of schizoid and obsessive-compulsive traits as a person becomes older.…”
Section: Dsm Personality Disorders: Cross-sectional Resultsmentioning
confidence: 82%
“…It comprises older people who, unlike subjects in the other groups, had few incarcerations in the last year, few offences without judicial intervention, relatively few psychiatric disorders, and, most particularly, no PD. It might be suggested that these differences are due solely to the more advanced age of people in this group as SUD,70 criminality,29 and cluster B PD71,72 have been consistently reported to decrease with age. Still, the small numbers of relationships and separations, psychiatric consultations and hospitalizations, and low criminal history scores strongly suggest that this group constitutes a distinct profile.…”
Section: Discussionmentioning
confidence: 90%
“…Cross-sectional and longitudinal studies of PD, however, have usually failed to find support for the level of stability implied by the DSM definitions. Cross-sectional studies have generally concluded that many PDs are less prevalent among older adults than younger and/or middle-aged adults (Cohen et al, 1994; Coid, Yang, Tyrer, Roberts, & Ullrich, 2006; Gutiérrez et al, 2012; Samuels et al, 2002; Segal, Hook, & Coolidge, 2001); and longitudinal evidence suggests that, on average, most PDs show mean-level decreases over time in both clinical (Ferro, Klein, Schwartz, Kasch, & Leader, 1998; Grilo et al, 2004) and nonclinical samples (Crawford et al, 2005; Johnson et al, 2000; Lenzenweger, Johnson, & Willett, 2004). In short, self-reported data suggest that many PDs do “become less evident or remit with age,” as stated in the DSM-IV-TR (American Psychiatric Association, 2000, p. 688).…”
mentioning
confidence: 99%